Effect of the smear layer on the filling of artificial lateral canals and microleakage - Andréa Gonçalves Moretti; Carlos Augusto de Morais Souto Pantoja; Danna Mota Moreira; Alexandre Augusto Zaia; José Flávio Affonso de Almeida (Universidade Estadual de Campinas, 2015)
Aim: To evaluate the influence of the smear layer on the filling and prevention of microleakage in artificial lateral canals after use of different irrigating solutions. Methods: Two lateral canals were produced in 44 human dental roots with drills of 0.1 mm in diameter. The roots were divided in 4 groups according to the irrigation protocol: GI - 0.9% saline solution (control); GII - 2.5% sodium hypochlorite + 17% EDTA; GIII - 2% chlorhexidine gel + 17% EDTA; GIV - 2% chlorhexidine solution + 17% EDTA. Four roots were used as negative (n=2) and positive (n=2) controls. Lateral condensation technique and AH Plus were used to fill the root canals. Digital buccolingual radiographs were exposed and after the sealer had set, the roots were immersed in Indian ink dye and then cleared in methyl salicylate. The extent of filling and microleakage were measured and the values analyzed statistically. Results: No difference was found in the percentage of filling and microleakage among the groups, regardless of the location of the artificial lateral canals and the irrigation protocol used. Twenty percent of lateral canals produced no radiographic images, but their filling was confirmed using the clearing technique. Conclusions: The presence or absence of the smear layer did not affect the filling ability and the prevention of microleakage in artificial lateral canals.